2018
DOI: 10.1002/hbm.24376
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‐specific age‐related decreased brain network diversity in cognitively healthy elderly: A whole‐brain data‐driven analysis

Abstract: Age‐related changes in functional brain network have been well documented. However, recent studies have suggested the nonstationary properties of the functional connectivity of the brain, and little is known about the changes of functional connectivity dynamics during aging. In this study, a two‐step singular value decomposition was introduced to capture the dynamic patterns of the time‐varying functional connectivity in different frequency intervals, and the whole‐brain and regional brain diversity were quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 67 publications
3
10
0
Order By: Relevance
“…The areas correlated with low age-related complexity are mainly located in the DN and frontoparietal control network. Importantly, unlike the other studies analyzed, here complexity is more closely related to a specific cognitive aspect such as mental flexibility, adding a putative neurophysiological mechanism of cognitive flexibility, or at least a closer link between BEN and cognition (Lou et al, 2019). This link is consistent with the general decrease of the neurocognitive flexibility in aging found both on a cognitive level and on a neural signal level.…”
Section: Brain Entropy In Physiological Agingsupporting
confidence: 80%
See 1 more Smart Citation
“…The areas correlated with low age-related complexity are mainly located in the DN and frontoparietal control network. Importantly, unlike the other studies analyzed, here complexity is more closely related to a specific cognitive aspect such as mental flexibility, adding a putative neurophysiological mechanism of cognitive flexibility, or at least a closer link between BEN and cognition (Lou et al, 2019). This link is consistent with the general decrease of the neurocognitive flexibility in aging found both on a cognitive level and on a neural signal level.…”
Section: Brain Entropy In Physiological Agingsupporting
confidence: 80%
“…Shannon entropy (SE) has been used to correlate BEN and aging, showing a decrease of age-related complexity in the whole brain as well as in the right inferior frontal gyrus, right amygdala, right hippocampus, and left parahippocampal gyrus at the frequency interval of 0.06–0.12 Hz ( Lou et al, 2019 ). However, this study points out that whole-brain resting state entropy reflects general cognitive flexibility and information processing, measured by typical executive functions neuropsychological tests.…”
Section: Entropy In Agingmentioning
confidence: 99%
“…Another study (Yin et al, 2016) found that age-related changes in the functional flexibility of the brain differ in different regions of the cerebral cortex. A recent study in 188 cognitively healthy elderly individuals (Lou et al, 2019) found that frequencyspecific brain network diversity decreased with increasing age at both the whole-brain and regional levels. Thus, exploring dynamic functional connectivity promises to enrich our knowledge of the functional organization of the brain, but little is known about changes in dynamic functional connectivity during aging.…”
Section: Introductionmentioning
confidence: 97%
“…It is also an important node of the DMN (Greicius et al, 2003). Previous aging studies have found age-related changes in the FC of this region and an association between these changes and cognitive decline in different domains, specifically, executive function (Lou et al, 2019;Zhao et al, 2020), semantic knowledge (Hoffman & Morcom, 2018), inhibitory control (Hu et al, 2018), and memory (Huo et al, 2018;Lamichhane et al, 2018). In line with our results, there is evidence of the loss of hub role for left IPC in aging, which was demonstrated using cortical thickness covariance networks (Carey et al, 2019).…”
Section: F I G U R Ementioning
confidence: 99%